COMPARATIVE STUDY OF PRIMARY SCHOOL ADMINISTRATORS' PERSPECTIVES ON INCLUSIVE EDUCATION OF DIFFERENTLY ABLED CHILDREN IN INDIA AND UZBEKISTAN - Ikrom Kizi, Tolipova Ranokhon; M, Harikrishnan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this study is to examine the current state of attitudes and practices of primary school administrators concerning inclusive education in two different countries Delhi, India and Tashkent, Uzbekistan with a comparative cross-sectional research design. The study seeks to establish the perception that the administrators have towards children with disabilities in regular schools as well as the factors that influence the perception. The purpose of the study is therefore to establish similarities and/or differences in the perceptions and practices of administrators from the two culturally and educationally distinct cities with regard to inclusive education. The participants were primary school administrators from public and government schools in Delhi and Tashkent to target the key persons responsible for supporting and coordinating inclusion in the schools. The sample was chosen with 677 male and 453 female administrators and 780 participants from Delhi, and 350 from Tashkent which provides a good mix of the participants’ views from different regions. The data were collected through survey; the questionnaire included questions on attitudes towards inclusion, training received, knowledge of policies in relation to inclusion, support and barriers. When the data was analyzed using SPSS software, it was found that there was a statistically significant difference in attitudes between the administrators in Delhi and those in Tashkent. Even with the similar training frequency in both the cities, the total training results are still unsatisfactory, which shows the requirement for more effective professional development. It also revealed that there were significant differences in the perceived availability of support systems and the challenges that were faced, which show that the regional policies and resource allocation have a big influence on the success of inclusive education. There was a difference in the perception among male and female administrators with the female administrators perceiving a higher impact of inclusive education and identifying more areas of need. These findings underscore the value of the contextualized approaches that take into consideration the particularities of various geographical and population settings.